Natural phenolic compounds from Satureja L. as inhibitors of COVID-19 protease (Mpro): Computational investigations - Faika Başoğlu-Ünal; Selin Tufan; Nur Tan (International Journal of Plant Based Pharmaceuticals, 2022)
Coronavirus (SARS-CoV-2) causes a new type of severe acute respiratory syndrome that first appeared in Wuhan in December 2019; it is a very fast-spreading and deadly virus. Therefore, urgent discovery or development of “lead compounds” against this virus is crucial. Natural compounds have always served as a great source, especially the use of traditional medicinal plants, in modern drug discovery. This study aimed to investigate the SARS-CoV-2 protease inhibition potential of the phenolic compounds in the genus Satureja L. The affinities of the chosen natural products were understood using molecular docking simulation against the SARS-CoV-2 protease enzyme. The study proved that three different phenolic compounds namely 5,6-dihydroxy-2-(4-hydroxy-3-methoxyphenyl)-7,8-dimethoxy-4H-chromen-4-one, 2-(3,4-dimethoxyphenyl)-5,6-dihydroxy-7,8-dimethoxy-4H-chromen-4-one, and 5,6-dihydroxy-2-(3-hydroxy-4-methoxyphenyl)-7,8-dimethoxy-4H-chromen-4-one obtained from Satureja L. taxa were found as promising against SARS-CoV-2 main protease.